2018
DOI: 10.18488/journal.aefr.2018.810.1239.1256
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Monetary Policy Instruments on Economic Growth: Evidence from Nigeria

Abstract: The inability of monetary policies to efficiently and effectively exploit its policy objective could be a function of the pitfall of policy instruments adopted which seems to restrict its contributions to economic advancement in Nigeria. It is on this premise that this study investigated the efficacy of monetary policy instruments in Nigeria using monthly data from year 2000 to 2016. The study adopted the Johansen Multivariate Cointegration approach and Vector Error Correction (VECM). The Cointegration test es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
2
5
0
Order By: Relevance
“…Interest rate has a positive and significant (10%) impact on economic growth during the study period. This finding is consistent with the findings of Adegbite and Alabi (2013), Ogbonna andUma (2017), andTule, Ogundele, andApinran (2018). A percent increase in the current rate of interest will increase economic growth in Nigeria by 0.42%.…”
Section: Model Interpretationsupporting
confidence: 91%
“…Interest rate has a positive and significant (10%) impact on economic growth during the study period. This finding is consistent with the findings of Adegbite and Alabi (2013), Ogbonna andUma (2017), andTule, Ogundele, andApinran (2018). A percent increase in the current rate of interest will increase economic growth in Nigeria by 0.42%.…”
Section: Model Interpretationsupporting
confidence: 91%
“…These outcomes gain support from the previous studies (e.g. Tule et al, 2018;Ufoeze et al, 2018;Fasanya et al, 2013), where they revealed that monetary policy instruments have a long-run relationship with economic growth in Nigeria. Yet, some studies (e.g.…”
Section: Monetary Policy and Economic Growthsupporting
confidence: 83%
“…Among others, a lack of privatization and capital account openness as well as an absence of competition in MENA banking systems are the main factors behind this negative effect (Anzoategui et al, 2010;Barajas et al, 2011). On the other hand, Maduka and Onwuka (2013) investigate the financial structure and economic growth nexus-both in the long and short runs-revealing that financial deepening has a negative and significant effect on economic growth, particularly in the case of Nigeria. Al-Malkawi and Abdullah (2011) find similar results for the United Arab Emirates (UAE), where they observe a negative relationship between FD and economic growth.…”
Section: Theoretical Background and Relevant Literature Surveymentioning
confidence: 99%